Dependence of the boundary heat flux width on core and edge profiles in Alcator C-Mod. (1st July 2022) - Ballinger, S.B.; Brunner, D.; Hubbard, A.E.; Hughes, J.W.; Kuang, A.Q.; LaBombard, B.; Terry, J.L.; White, A.E.
Abstract: This work presents new evidence that the heat flux width, λ q, in the Alcator C-Mod tokamak scales with the edge electron pressure, as observed in the ASDEX Upgrade (AUG) tokamak (Silvagni et al 2020 Plasma Phys. Control. Fusion 62 045015), but the scaling with volume-averaged pressure, p ¯, from the plasma stored energy, found by Brunner et al (2018 Nucl. Fusion 58 094002), is a better predictor of λ q in Alcator C-Mod than the edge electron pressure. These previous studies, which find that λ q decreases with increasing plasma pressure, imply that a high performance core at high pressure will lead to challenging heat and particle exhaust due to very small λ q . This concern has led to our significant enlargement of the C-Mod database with the electron density, temperature, and pressure profile data from the Thomson scattering and electron cyclotron emission diagnostics. Using the C-Mod database augmented with new profile data, we find that λ q decreases with increasing edge electron pressure as λ q ∝ p e, 95 − 0.26, similar to results from AUG, and showing the strength of cross-machine comparisons. We also find that λ q ∝ p e, c o r e − 0.56, consistent with the original finding from C-Mod that the heat flux width scales as p ¯ − 0.48 (Brunner et al 2018 Nucl. Fusion 58 094002). The scalings of λ q with separatrix pressure and gradient scale length are found to match the AUG results qualitatively. The C-Mod scalings with edge plasma quantities have more scatter than the p ¯ scaling, and, importantly, show different trends for H-modes relative to L- and I-mode. Investigating the source of this discrepancy presents an opportunity for further study that may improve our ability to predict the heat flux width in different confinement scenarios in the pursuit of optimizing core-edge performance in future reactors.